PERBANDINGANÃÂ MODELÃÂ PEMBELAJARANÃÂ KONVENSIONALÃÂ DANÃÂ KOOPERATIFÃÂ TIPEÃÂ JIGSAWÃÂ TERHADAPÃÂ HASILÃÂ BELAJARÃÂ KOMPETENSIÃÂ PERBAIKANÃÂ SISTEMÃÂ PENGAPIANÃÂ ÃÂ ÃÂ - UtomoÃƒÂ‚Ã‚Â , Prasetyo; Winarno, -; SuwahyoÃƒÂ‚Ã‚Â , - (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2008)
TujuanÃÂ dariÃÂ penelitianÃÂ iniÃÂ adalahÃÂ untukÃÂ membandingkanÃÂ hasilÃÂ belajarÃÂ kompetensiÃÂ perbaikanÃÂ sistemÃÂ pengapianÃÂ yangÃÂ pembelajarannyaÃÂ disampaikanÃÂ denganÃÂ menggunakanÃÂ modelÃÂ pembelajaranÃÂ konvensionalÃÂ danÃÂ modelÃÂ kooperatifÃÂ tipeÃÂ Jigsaw.ÃÂ PopulasiÃÂ dalamÃÂ penelitianÃÂ iniÃÂ adalahÃÂ 108ÃÂ orangÃÂ siswaÃÂ kelasÃÂ XÃÂ TeknikÃÂ MekanikÃÂ OtomotifÃÂ (TMO)ÃÂ SMKÃÂ NegeriÃÂ 4ÃÂ SemarangÃÂ tahunÃÂ AjaranÃÂ 2008/2009ÃÂ yangÃÂ terdiriÃÂ atasÃÂ 36ÃÂ siswaÃÂ kelasÃÂ XÃÂ TMOÃÂ 1,ÃÂ 36ÃÂ siswaÃÂ kelasÃÂ XÃÂ TMOÃÂ 2,ÃÂ danÃÂ 36ÃÂ siswaÃÂ kelasÃÂ XÃÂ TMOÃÂ 3.ÃÂ PenelitianÃÂ iniÃÂ adalahÃÂ penelitianÃÂ eksperimenÃÂ denganÃÂ desainÃÂ ControlÃÂ groupÃÂ preÃÂtestÃÂpostÃÂtest.ÃÂ HasilÃÂ belajarÃÂ pembelajaranÃÂ menggunakanÃÂ modelÃÂ pembelajaranÃÂ kooperatifÃÂ tipeÃÂ jigsawÃÂ mengalamiÃÂ peÃ¢â¬ÂningkatanÃÂ dariÃÂ perolehanÃÂ rataÃ¢â¬ÂrataÃÂ awalÃÂ sebesarÃÂ 68,49ÃÂ menjadiÃÂ 83,17ÃÂ setelahÃÂ pembelajaran.ÃÂ ÃÂ PeningkatanÃÂ iniÃÂ menÃ¢â¬ÂcapaiÃÂ 56,11%.ÃÂ PeningkatanÃÂ hasilÃÂ belajarÃÂ kelompokÃÂ kontrolÃÂ hanyaÃÂ mencapaiÃÂ 24,73%;ÃÂ yaituÃÂ dariÃÂ kemampuanÃÂ awalÃÂ sebesarÃÂ 68,57ÃÂ menjadiÃÂ 78,81.ÃÂ HalÃÂ iniÃÂ menunjukkanÃÂ bahwaÃÂ hasilÃÂ belajarÃÂ yangÃÂ pembelajarannyaÃÂ menggunakanÃÂ modelÃÂ pembelajaranÃÂ kooperatifÃÂ tipeÃÂ jigsawÃÂ lebihÃÂ baikÃÂ dibandinganÃÂ denganÃÂ modelÃÂ konvensional. ÃÂ KataÃÂ Kunci:ÃÂ KooperatifÃÂ tipeÃÂ Jigsaw,ÃÂ konvensionalÃÂ danÃÂ hasilÃÂ belajar.TheÃÂ objectiveÃÂ ofÃÂ thisÃÂ researchÃÂ isÃÂ toÃÂ compareÃÂ betweenÃÂ theÃÂ studyÃÂ resultÃÂ withÃÂ repairÃÂ ignitionÃÂ systemÃÂ competenceÃÂ inÃÂ whichÃÂ theÃÂ learningÃÂ isÃÂ presentedÃÂ usingÃÂ conventionalÃÂ andÃÂ jigsawÃÂ cooperativeÃÂ learningÃÂ model.ÃÂ TheÃÂ populationÃÂ ofÃÂ theÃÂ researchÃÂ wasÃÂ 108ÃÂ studentsÃÂ ofÃÂ tenthÃÂ gradeÃÂ inÃÂ AutomotiveÃÂ MechanicalÃÂ EngineeringÃÂ (TMO)ÃÂ atÃÂ SMKÃÂ NegeriÃÂ 4ÃÂ SemarangÃÂ yearÃÂ 2008/2009ÃÂ thatÃÂ couldÃÂ beÃÂ dividedÃÂ intoÃÂ 36ÃÂ tenthÃÂ gradersÃÂ ofÃÂ TMOÃÂ 1,ÃÂ 36ÃÂ tenthÃÂ gradersÃÂ ofÃÂ TMOÃÂ 2,ÃÂ andÃÂ 36ÃÂ tenthÃÂ gradersÃÂ ofÃÂ TMOÃÂ 3.ÃÂ ThisÃÂ researchÃÂ isÃÂ experimentalÃÂ oneÃÂ withÃÂ ControlÃÂ GroupÃÂ PreÃÂTestÃÂPostÃÂTestÃÂ design.ÃÂ TheÃÂ studentÃÂ reÃ¢â¬ÂsultÃÂ usingÃÂ cooperativeÃÂ learningÃÂ modelÃÂ jigsawÃÂ typeÃÂ getsÃÂ improvementÃÂ fromÃÂ firstÃÂ averageÃÂ gainingÃÂ aboutÃÂ 68,49ÃÂ toÃÂ 83,17ÃÂ afterÃÂ learning.ÃÂ ThisÃÂ improvementÃÂ percentageÃÂ achievesÃÂ 56,11%.ÃÂ Meanwhile,ÃÂ theÃÂ studyÃÂ resultÃÂ improvementÃÂ percentageÃÂ inÃÂ controlledÃ¢â¬ÂgroupÃÂ onlyÃÂ achievesÃÂ 24,73%.ÃÂ ItÃÂ isÃÂ fromÃÂ firstÃÂ abilityÃÂ aboutÃÂ 68,57ÃÂ toÃÂ 78,81.ÃÂ ItÃÂ showsÃÂ thatÃÂ theÃÂ studyÃÂ resultÃÂ usingÃÂ jigsawÃÂ cooperativeÃÂ learningÃÂ modelÃÂ isÃÂ betterÃÂ thatÃÂ theÃÂ conventionalÃÂ one. ÃÂ Keywords:ÃÂ jigsawÃÂ cooperativeÃÂ model,ÃÂ conventionalÃÂ andÃÂ studyÃÂ result